Corpus linguistics and language testing: Navigating uncharted waters. (October 2017) - Egbert, Jesse
The use of corpora and corpus linguistic methods in language testing research is increasing at an accelerated pace. The growing body of language testing research that uses corpus linguistic data is a testament to their utility in test development and validation. Although there are many reasons to be optimistic about the future of using corpus data in language testing, the convergence of these two fields introduces uncharted waters that should be traversed carefully to ensure that high standards of methodological rigor are maintained. The objectives of this paper are as follows: (1) to describe and evaluate the ways corpora and corpus data have been used in language testing to date; and (2) to offer recommendations for best practices to encourage rigorous and appropriate corpus linguistic methods for language testing purposes. This is accomplished with the aid of examples from papers in this special issue, as well as other previous work in this area. The future holds great promise for a useful methodological synergy between corpus linguistics and language testing. The choices researchers make as they navigate the uncharted and challenging waters that lie ahead will ultimately determine whether that potential is fully realized.